2003
DOI: 10.1136/tc.12.2.227
|View full text |Cite
|
Sign up to set email alerts
|

The impact of learning of a genetic predisposition to nicotine dependence: an analogue study: Table 1

Abstract: Objectives: To examine the consequences of informing smokers of a genetic predisposition to nicotine dependence and of providing treatment efficacy information tailored to genetic status. Design: Analogue study using four vignettes; 2 (genetic status) × 2 (whether treatment efficacy information provided) between subjects design. Participants: 269 British adult smokers. Outcome measures: Preferred cessation methods and perceived control over quitting. Results: Gene positive participants were significantly more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 12 publications
2
73
2
Order By: Relevance
“…Although genetic testing for obesity risk is not yet available, genetic research in obesity may lead to susceptibility testing in the future (5). Consequently, we utilized a common vignette paradigm that asks individuals to consider different hypothetical scenarios for testing (6). We used the Theory of Planned Behavior as our conceptual model (7).…”
Section: Introductionmentioning
confidence: 99%
“…Although genetic testing for obesity risk is not yet available, genetic research in obesity may lead to susceptibility testing in the future (5). Consequently, we utilized a common vignette paradigm that asks individuals to consider different hypothetical scenarios for testing (6). We used the Theory of Planned Behavior as our conceptual model (7).…”
Section: Introductionmentioning
confidence: 99%
“…8 For example, informing young smokers they have a genetic predisposition to nicotine dependence may undermine their efficacy to quit and amount of effort spent on planning and trying to quit. 8 Consistent with this view, using hypothetical vignettes, smokers informed they had a genetic variant related to increased nicotine dependence reported less use of willpower as a means to quit, 9 although perceived control over their ability to quit was not influenced by the feedback. In another study, adult smokers who attributed their smoking to genetic causes reported lower control over smoking, although such attribution did not predict cessation success.…”
Section: Introductionmentioning
confidence: 66%
“…Also, offering treatment advice on the basis of a genetic test to an individual who subsequently fails to stop smoking may result in reduced motivation to make further attempts (Munafò, Lerman, Niaura, Shields, & Swan, 2005;. Although no data currently exist to test this possibility directly, analogue studies suggest genetic feedback may decrease the perceived value of will-power in a cessation attempt (Wright et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recommending bupropion on the basis of the results of a genetic test may encourage patients who would otherwise be reluctant to use this pharmacotherapy to do so. This possibility will require independent testing, possibly using analogue methods (Wright, Weinman, & Marteau, 2003).…”
Section: Discussionmentioning
confidence: 99%